Digital media vs mainstream media: Exploring the influences of media exposure and information preference as correlates of media credibility (2020)
Rapid advancements in new media technologies have empowered presumed inactive mass media consumers to become active content creators on digital media platforms. The overarching implication of this unprecedented opportunity on media credibility has continued to reverberate among researchers, media practitioners, and media users. This study, employing selective exposure and McLuhan's 'medium is the message' frameworks as theoretical underpinnings, examined the influence of media exposure pattern and information preferences on perception of mainstream and digital media credibility among the University of Ibadan undergraduates. Cross sectional survey and focus group discussions (FGDs) served as the study designs while cluster probability and purposive sampling techniques were employed to select respondents and discussants who participated in the study. Analysis of both quantitative and qualitative data revealed that the mainstream media were adjudged more credible despite heavier dependency on digital media for information. Frequency of media exposure and information preferences on both media platforms have predictive influences on respondents’ credibility evaluation. Specifically, one of the significant conclusions of the study is that audience credibility judgement, predicted by frequent exposure and choice of content consumption, are grounded on the awareness of the implicit nature of media platforms.